Sulforaphane inhibits growth and blocks Wnt/β-catenin signaling of colorectal cancer cells - Bernkopf, Dominic; Daum, Gabriele; Brückner, Martina; Behrens, Jürgen (Oncotarget, 2018)
The naturally occurring isothiocyanate sulforaphane (SFN) from cruciferous vegetables is associated with growth inhibition of various cancer types, including colorectal cancer. Colorectal cancer is most frequently driven by hyperactive Wnt/β-catenin signaling. Here, we show that SFN treatment reduced growth of three unrelated colorectal cancer cell lines (SW480, DLD1 and HCT116) via induction of cell death and inhibition of proliferation. Importantly, SFN inhibits Wnt/β-catenin signaling in colorectal cancer cells as shown by inhibition of β-catenin-dependent luciferase reporters and repression of β-catenin target genes (AXIN2, LGR5). SFN inhibits Wnt signaling downstream of β-catenin degradation and induces the formation of nuclear β-catenin structures associated with closed chromatin. Co-expression of the transcription factors LEF1 or TCF4 prevented formation of these structures and rescued inhibition of Wnt/β-catenin signaling by SFN. Our findings provide a molecular basis explaining SFN effects in colorectal cancer cells and underline its potential for prevention and therapy of colorectal cancer.
EVALuna2:34943